If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2p + -5e) = (3p + 6r) + (p + -1r) Reorder the terms: (-5e + 2p) = (3p + 6r) + (p + -1r) Remove parenthesis around (-5e + 2p) -5e + 2p = (3p + 6r) + (p + -1r) Remove parenthesis around (3p + 6r) -5e + 2p = 3p + 6r + (p + -1r) Remove parenthesis around (p + -1r) -5e + 2p = 3p + 6r + p + -1r Reorder the terms: -5e + 2p = 3p + p + 6r + -1r Combine like terms: 3p + p = 4p -5e + 2p = 4p + 6r + -1r Combine like terms: 6r + -1r = 5r -5e + 2p = 4p + 5r Solving -5e + 2p = 4p + 5r Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '-2p' to each side of the equation. -5e + 2p + -2p = 4p + -2p + 5r Combine like terms: 2p + -2p = 0 -5e + 0 = 4p + -2p + 5r -5e = 4p + -2p + 5r Combine like terms: 4p + -2p = 2p -5e = 2p + 5r Divide each side by '-5'. e = -0.4p + -1r Simplifying e = -0.4p + -1r
| 2x^2-7x-4=1586 | | 20+0.15t=30+10t+0.25 | | 45r+60=285 | | 2x=72-28 | | 4x+11x= | | (5x+2y)*(5x+2y)=(5x+2y)*(5x+2y) | | 4r+3(r+2)= | | (5w-1)(6w+3)= | | 4(s-1.4)=2 | | 3g-2=1 | | (2*x)*x=50 | | h=-16t^2+138t+82 | | 9x+14X+12X+115=360 | | 180=3x-2+4x-18+x | | 20+0.15t=30+10t+25 | | 57=29-4(x-4) | | -1x^2-4x-1=0 | | 2b+4.1=2.9 | | 3(a-6)+9(7-a)= | | -148+8x=41-x | | h=-16t^2+138+82 | | (5x+2y)squared=2 | | -16t^2+104t+56=104 | | .05(70x+100)-50=.04(90x+200)+50 | | 6x=14+16 | | 2(4y-1)-3y=12 | | 1.25r+6.75=31.75 | | 4x+-7x=13 | | -7-7k=-7(1+k) | | -2(m-3)=-6m | | 8(x+1)+11.6=9 | | 3m+1=6m-8 |